Remote Detection and Visualization of Surface Traces of Nitro-Group-Containing Explosives - Sergei Bobrovnikov; Evgeny Gorlov; Viktor Zharkov (Photonics)
This paper presents the results of an experimental study of the possibility of remote visualization of traces of some nitro-group-containing explosives (TNT, RDX, HMX, Composition-B, and Tetryl) on the surface of aluminum foil using the laser fragmentation/laser-induced fluorescence (LF/LIF) method. A tunable excimer KrF laser with a narrow generation line was used to fragment explosives and excite fluorescence of their NO fragments (nitric oxide molecules) from the second vibrationally excited state (v″ = 2). When recording optical responses, spectral selection of the γ(0, 0) fluorescence band of NO was carried out. The LF/LIF method is shown to be promising for creating scanning detectors that will allow remote detection of trace amounts of explosives with a concentration of up to 1 μg/cm2 on the surfaces of objects at a distance of several meters and simultaneously determine their location. The sensitivity of the one-color LF/LIF detection method can be increased by increasing the energy density of the probing radiation and/or by optimizing the LF/LIF excitation process.